Exploring an Unexamined Source of Racial Disparities in Juvenile Court Involvement: Unexcused Absenteeism Policies in U.S. Schools. (March 2021) - McNeely, Clea A.; Alemu, Besufekad; Lee, Won Fy; West, Isis
This two-part study explored whether discrimination encoded into U.S. school absenteeism policies leads to racially minoritized students being overrepresented in the juvenile court system. First, we examined unexcused absenteeism policies in a nationally representative school district sample ( n = 97). All districts excused absences for reasons White students often miss school but not necessarily for reasons racially minoritized students do. Next, in three school districts we documented large racial disparities in both the proportion of absences designated unexcused (Whites 13%, Asians 18%, Hispanics 21%, Blacks 24%, and American Indians 24%) and risk of court petition for truancy, even after accounting for the total number of absences: Whites hazard ratio (HR) = 1.0; Asians HR = 1.15, 95% confidence interval (CI) [0.98, 1.36]; Hispanics HR = 1.60, 95% CI [1.34, 1.92]; Blacks HR = 2.17, 95% CI [1.88, 2.50]; and American Indians HR = 3.94, 95% CI [3.12, 4.97]. Disproportionality in unexcused absenteeism fully explained the Hispanic/White and partially explained the Black/White and American Indian/White court petition disparities.